Efficacy and safety of sequential immunosuppressive treatment for severe IgA nephropathy: A retrospective study - Mian-Na Luo; Mian-Na Luo; Qingjun Pan; Ting Ye; Shangmei Li; Lawei Yang; Hua-Feng Liu; Hua-Feng Liu; Yongzhi Xu (Frontiers Media S.A., 2023)
Background: This study compared the efficacy and safety of sequential immunosuppressive therapy in patients with non-end-stage IgA nephropathy (IgAN) with Lee's classification of IV ∼ V and provided evidence for the use of immunotherapy in patients with severe IgAN.Methods: We retrospectively analyzed the clinical data of patients with Lee's IV ∼ V non-end-stage IgA nephropathy.Results: 436 patients were diagnosed with IgAN, and 98 patients who met the inclusion criteria were included in this retrospective study. Of these, 17 were in the supportive care group, 20 in the P group (prednisone-only), 35 in P + CTX group (the prednisone combined with cyclophosphamide followed by mycophenolate mofetil), and 26 in the P + MMF group (prednisone combined with mycophenolate mofetil). The four groups showed differences in the segmental glomerulosclerosis score and the proportion of patients with Lee's grade IV (p < 0.05), but no differences in other indicators. Compared with the baseline values, urine protein-to-creatinine ratio (PCR) significantly decreased and serum albumin increased (p < 0.05), but there was no significant difference between the groups. The estimated Glomerular Filtration Rate (eGFR) of the P, P + MMF, and P + CTX groups were higher than that of the supportive care group at the 6th and 24th month after treatment (all p < 0.05). At the 24th month, the eGFR in the P + CTX group was higher than that in the P + MMF group (p < 0.05). The effective remission rate of the P + CTX group was higher than that of the supportive care group (p < 0.05). At 12 months, the effective remission rate of the P group was higher than that of the supportive care group (p < 0.05). At the 24th month, there was no significant difference in the effective remission rates among the three groups (P, P + MMF, and P + CTX). Nine patients with severe IgA nephropathy reached the endpoint.Conclusion: This study showed that immunosuppressive therapy insevere IgAN patient scan effectively reduce urinary protein, increase albumin, and protect renal function in the early stages of IgAN. P + CTX is the most commonly used, which has a high effective remission rate of urine protein and a low incidence of end-point events.